Negocios inclusivos. como estrategia de responsabilidad social empresarial para la inclusión laboral de los desplazados en el Magdalena (2014)
In the context of corporate social responsibility emerges inclusive business model as a strategy of private and public sector for the inclusion of vulnerable populations in the political, economic and social dynamics of productive society; in order to develop their intellectual, human and labor potential and facilitate sustainability and economic autonomy; to contribute significantly to improving the quality of life and productivity of these populations; and therefore, in economic and social development of their local environment. This article analyzes the that affect on corporate social responsibility in the most representative companies in the department of Magdalena and possible strategies to the implementation inclusive business model; specifically in the aspect of employment inclusion of displaced population, to contribute that way with to improving in the quality of life and development of this region.